A Destination-Based Allowance for Corporate Equity - Hebous, Shafik (IMF Working Papers; Working Paper, 2018)
Following renewed academic and policy interest in the destination-based principle for taxing profits-particularly through a destination-based cash flow tax (DBCFT)-this paper studies other forms of efficient destination-based taxes. Specifically, it analyzes the Destination-Based Allowance for Corporate Equity (DBACE) and Allowance for Corporate Capital (DBACC). It describes adjustments that are required to turn an origin into a destination-based versions of these taxes. These include adjustments to capital and equity, which are additional to the border adjustments needed under a DBCFT. The paper finds that the DBACC and DBACE reduce profit shifting and tax competition, but cannot fully eliminate them, with the DBACE more sensitve than the DBACC. Overall, given the potential major political cost of switching from an origin to a destination-based tax system, we conclude that advantages of the DBCFT are likely to outweigh the transitional advantages of the DBACE/DBACC.